Simulation Analysis of Interface Circuits for Piezoelectric Energy Harvesting with Damped Sinusoidal Signals and Random Signals - Shuai Pang; Wenbin Li; Jiangming Kan (Universitas Ahmad Dahlan, 2015)
Various interface circuits for collecting the energy of piezoelectric cantilever beams have been widely investigated. Such circuits include the standard interface, series synchronized switch harvesting interface circuit, parallel synchronized switch harvesting interface, synchronized charge extraction interface, and others. Most studies focus on the performance of different interface circuits with standard sinusoidal excitations. However, in real situations where constant harmonic vibrations are not present, the equivalent voltage from piezoelectric cantilever beams with excitations is not necessarily sinusoidal. In the present study, a simulation analysis of four different interface circuits with signal sources that are both damped sinusoidal and random was performed using Matlab and PSpice. The results show that the interface circuits have improved performance under low load resistance values with damped sinusoidal signal. In addition, the parallel and series synchronized switch harvesting interface circuits may perform well in collecting piezoelectric energy with random excitations.